Bifunctional One‐Component Catalysts for the Addition of Carbon Dioxide to Epoxides. Issue 3 (9th December 2014) - Büttner, Hendrik; Lau, Kornelia; Spannenberg, Anke; Werner, Thomas
Abstract Several bifunctional ammonium salts were synthesized and employed as one‐component catalysts for the conversion of CO2 and epoxides to produce cyclic carbonates. These catalysts show superior activities compared to their monofunctional analogs. A turnover number of up to 693 and a turnover frequency of up 392 h−1 could be achieved for the best catalyst. Moreover, the effect of various solvents has been studied. All employed solvents and the product formed had a negative influence on substrate conversion. The scope and limitation of the reaction has been studied carefully for two general reaction protocols at 45 and 90 °C. In over 20 examples, the isolated yields after filtration were 90 %. In addition, we present the first organocatalyzed synthesis of a cyclohexene‐based naturally occurring cyclic carbonate, and its molecular structure was determined by XRD. Furthermore, we demonstrate that the reaction can be performed even on a multigram scale and can be monitored by in situ FTIR spectroscopy.